Thermal tolerance depends on season, age and body condition in imperilled redside dace Clinostomus elongatus. Issue 1 (24th July 2020) - Turko, Andy J; Nolan, Colby B; Balshine, Sigal; Scott, Graham R; Pitcher, Trevor E
Abstract: Urbanization tends to increase water temperatures in streams and rivers and is hypothesized to be contributing to declines of many freshwater fishes. However, factors that influence individual variation in thermal tolerance, and how these may change seasonally, are not well understood. To address this knowledge gap, we studied redside dace Clinostomus elongatus, an imperilled stream fish native to rapidly urbanizing areas of eastern North America. In wild redside dace from rural Ohio, USA, acute upper thermal tolerance (i.e. critical thermal maximum, CTmax) ranged between 34°C in summer (stream temperature 22°C) and 27°C in winter (stream temperature 2°C). Juveniles had higher CTmax than adults in spring and summer, but in winter, CTmax was higher in adults. Thermal safety margins (CTmax − ambient water temperature; 11°C) were less than the increases in peak water temperature predicted for many redside dace streams due to the combined effects of climate change and urbanization. Furthermore, behavioural agitation occurred 5–6°C below CTmax. Safety margins were larger (>20°C) in autumn and winter. In addition, redside dace were more sensitive (2.5°C lower CTmax) than southern redbelly dace Chrosomus erythrogaster, a non-imperilled sympatric cyprinid. Body condition (Fulton's K ) of adult redside dace was positively correlated with CTmax, but in juveniles, this relationship was significant only in one of two summers of experiments. Next, we measured CTmax of captive redside dace fed experimentally manipulated diets. In adults, but not juveniles, CTmax was higher in fish fed a high- vs. low-ration diet, indicating a causal link between nutrition and thermal tolerance. We conclude that redside dace will be challenged by predicted future summer temperatures, especially in urbanized habitats. Thus, habitat restoration that mitigates temperature increases is likely to benefit redside dace. We also suggest habitat restoration that improves food availability may increase thermal tolerance, and thus population resilience.